Self-Government and the Prohibition of General Elections Under Baduy-Dalam Customary Law - Jumanah, Jumanah; Nugroho, Arif (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This article discusses the implementation of self-governance using customary law within the Baduy-Dalam Traditional Law Community (KMHA). The author's interest in studying the Baduy-Dalam stems from the bias in understanding between the KMHA, Villages, and Traditional Villages due to the regulation of Law No. 6 of 2014. One of the causes of this bias is the government's misunderstanding in treating and respecting the Baduy-Dalam KMHA, such as the General Election Commission's outreach in Baduy to encourage the participation of indigenous peoples in elections. This article aims to examine the existence and constitutionality of the Baduy-Dalam Tribe as a self-governing KMHA using customary law, including the legality if they do not participate in elections. The data used in this study are empirical facts about the characteristics of the KMHA, verified using a descriptive method with a qualitative approach. The study results show that the Baduy-Dalam Tribe meets the characteristics of a KMHA, making them suitable for self-governance with customary law, including celebrating democracy according to their customs. The novelty found is the full recognition of their unique customary governance system. In conclusion, the Baduy-Dalam Tribe remains constitutional as a self-governing KMHA using customary law. As a solution, the state must genuinely recognize, respect, and preserve their existence.